DESCRIPTION OF THE KNOWLEDGE OF CAT OWNERS ABOUT HOW TO PREVENT DISEASE IN THEIR PET CAT DURING THE COVID-19 PANDEMIC - Siagian, Tetty Barunawati (IPB University, 2023)
The number of cat owners has increased in Indonesia during the Covid 19 pandemic. The problem faced by cat owners in caring for their pet cats is a lack of knowledge about how to prevent disease. The research aims to identify the level of knowledge of cat owners about how to prevent disease during the Covid 19 pandemic. The research used a questionnaire to 100 cat owners who came to the WMB Satwa Clinic. The characteristics of the respondents who were recorded showed that the most cat owners were aged 17-25 years, dominated by women, had an undergraduate/graduate degree/doctoral degree, student work, and the number of cats kept was 1-2. The results of the study show that the knowledge of cat owners about how to prevent cat disease during the Covid 19 pandemic can be said to be quite good. This is based on the results of the questionnaire such as the owner has carried out complete vaccinations (26%) and annual vaccinations (21%) on their pet cats. The owner has provided routine treatments in the form of flea medication, worm medicine, and vitamins as much as 57.3%. Owners have sterilized their pet cats as much as 76%.